Cardiovascular Strain of Firefighting and the Risk of Sudden Cardiac Events. Issue 3 (July 2016) - Smith, Denise L.; DeBlois, Jacob P.; Kales, Stefanos N.; Horn, Gavin P.
Abstract : Approximately 45% to 50% of line-of-duty deaths in the fire service are caused by sudden cardiac deaths, which most often occur during or shortly after firefighting duties. We present a theoretical model linking the cardiac, vascular, and hematological responses of firefighting to the triggering of sudden cardiac death in susceptible individuals. Abstract : Cardiac death within the fire service results from a complicated interaction between cardiac, vascular, and hematological responses to firefighting duties and underlying disease.